2019
DOI: 10.1016/j.gaitpost.2018.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics can help to discriminate the implication of iliopsoas, hamstring and gastrocnemius contractures to a knee flexion gait pattern

Abstract: Background: Excessive Knee Flexion Gait Pattern (KFGP) is a common gait deviation in many pathological conditions. The contractures of the muscles that have been identified as being responsible of KFGP are: iliopsoas, hamstring and gastrocnemius. Research question:How do isolated contractures of the iliopsoas, hamstrings and gastrocnemius impact knee flexion during gait?Methods: Three levels of contracture (mild, moderate and severe) were simulated bilaterally using an exoskeleton on 10 healthy participants fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In humans, the short-term effects (immediate to a few minutes following application) of artificial joint constraints have been studied using external devices. For example, to mimic the knee flexion contracture gait pattern typical for people with cerebral palsy and people with knee arthropathy and to mimic full knee extension following knee arthrodesis surgery (44)(45)(46)(47)(48)(49)(50)(51)(52). A simulated knee flexion contracture results in an increased forefoot weight bearing and flexion posture during stance, increasing the knee extensor torque (46,48,51).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the short-term effects (immediate to a few minutes following application) of artificial joint constraints have been studied using external devices. For example, to mimic the knee flexion contracture gait pattern typical for people with cerebral palsy and people with knee arthropathy and to mimic full knee extension following knee arthrodesis surgery (44)(45)(46)(47)(48)(49)(50)(51)(52). A simulated knee flexion contracture results in an increased forefoot weight bearing and flexion posture during stance, increasing the knee extensor torque (46,48,51).…”
Section: Introductionmentioning
confidence: 99%
“…A simulated knee flexion contracture results in an increased forefoot weight bearing and flexion posture during stance, increasing the knee extensor torque (46,48,51). Both simulated knee flexion contracture and knee arthrodesis change ankle and hip kinematics to facilitate foot clearance of the braced limb (44)(45)(46)(48)(49)(50). Only one previous study reported short-term changes in EMG in response to an artificial knee flexion contracture and found an increase in the amplitude and duration of the gluteus maximus, vastus lateralis, and soleus muscles during the stance (46).…”
Section: Introductionmentioning
confidence: 99%